Coumarin based highly selective "off-on-off" type novel fluorescent sensor for Cu2+ and S2? in aqueous solution - Elmas, Şürkiye Nihan Karuk; Özen, Furkan; Koran, Kenan; Yılmaz, İbrahim; Görgülü, Ahmet Orhan; Erdemir, Serkan (My University, 2017)
Solvent free synthesis of 6,7-dihydroxy-3-(3- chlorophenyl) coumarin (CFHC) was designed and obtained by the interaction of 2-(2,4,5-trimethoxyphenyl)- 1-(3-chlorophenyl)acrylonitrile with pyridinium hydrochloride in the presence of silica gel by using microwave irradiation. The characterization of CFHC was confirmed by FT-IR, 1H, 13C, 13C–APT and 2D HETCOR spectroscopy methods. The optical behavior of CFHC towards metal ions was investigated by UV-visible and fluorescence spectroscopy. CFHC showed Bon–off^ type fluorescence response towards Cu2+ with high selectivity in aqueous solution (CH3CN/H2O, 9/1, v/v). Once binding with Cu2+, CFHC-Cu2+ complex also displayed high selectivity for sulfide, resulting in Boff–on^ type sensing of sulfide anion.
Coumarin tabanlı yüksek seçimli "off-on-off" tip sulu çözeltide Cu2 + ve S2- için yeni floresan sensör
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Makale - Yabancı Dilde Makale
Keywords: Coumarin; Fluorescent; Sensor; Copper; Sulfide